Answer:
this difference indicates that the results are independent but not reliable.
We're given the algebraic expression 2x^2 - 2z^4 + y^2 - x^2 + z^4
By hypothesis, x = -4, y = 3 and z = 2
Let's replace each letter by its given value:
2x^2 - 2z^4 + y^2 - x^2 + z^4
2(-4)^2 - 2(2)^4 + (3)^2 - (-4)^2 + (2)^4
(2*16) - 2*16 + 9 - 16 + 16
32 - 32 + 9 - 16 + 16
9
So wrong. The correct answer is not -3, but 9.
Hope this helps! :D
Answer:
22
Step-by-step explanation:
Answer:
<h2><u>
=</u>
<u>
57
/ 514 </u>
<u>
(Decimal: 0.110895)</u></h2>
Step-by-step explanation:
57
/ 514
<u>= 57
/ 514
</u>
<u>(Decimal: 0.110895)</u>
<u></u>
<u></u>
<u></u>
<u></u>
<u></u>
<u></u>
<u></u>
<u></u>
<u></u>
<h2><u>
And if that is not what you are looking for here: </u></h2><h2><u>
</u></h2>
Rewrite the equation as
x
/14
= 5/
7
. x/
14
= 5/
7
Multiply both sides of the equation by
14.14 ⋅ x
/14
= 14
⋅
5
/7
Simplify both sides of the equation.
Tap for fewer steps...
Cancel the common factor of 14
.
Cancel the common factor.
14
⋅ x
/14
= 14
⋅
5
/7
Rewrite the expression.
x
=
14
⋅
5
/7
Simplify 14
⋅ 5/
7
.
Cancel the common factor of 7
.
Factor 7 out of 14
.
x
=
7
(
2
)
⋅
5/
7
Cancel the common factor.
x
=
7
⋅ 2
⋅ 5/
7
Rewrite the expression.
x =
2
⋅
5
Multiply 2 by 5
.
<u>x
=
10</u>